Clinical Features of Spinal Cord Hemangioblastoma in a Dog - Michaels, Jennifer; Thomas, William; Ferguson, Sylvia; Hecht, Silke (Frontiers in Veterinary Science, 2015)
A 2-year-old male, intact Yorkshire terrier presented with a 1-month history of progressive paraparesis. Neurological examination revealed paraplegia with absent deep pain perception, decreased right pelvic limb withdrawal reflex, and lumbar pain consistent with an L4–S2 neurolocalization. Magnetic resonance imaging (MRI) showed a single, well-demarcated, intramedullary mass centered over the L3–4 disk space. A hemilaminectomy was performed, and the mass was removed en bloc. Histopathological evaluation was consistent with a hemangioblastoma. Follow-up MRI 9 months after surgery showed no evidence of tumor recurrence, and the dog was ambulatory paraparetic at that time. This case is consistent with a previous histopathological report of spinal cord hemangioblastoma in a dog and provides additional clinical information regarding diagnosis, treatment, and outcome associated with this tumor type.